Optimizing Fuel Rail Stability: An Examination of Vibration Levels with Different Clamp Configurations - Aneesh Kaliyanda; Binay Singh (North American Journal of Engineering Research, 2022)
This study explores the impact of clamping configuration on the vibrational behavior of a diesel engine fuel rail, focusing onwhether a two-clamp setup can effectively replace the traditional three-clamp arrangement without compromising system stability.The fuel rail, integral to the high-pressure fuel injection system, must withstand significant vibrations while maintaining precisefuel delivery. The research uses 11 accelerometers and a Rail Pressure Sensor (RPS) to investigate vibrational responses acrossdifferent clamping configurations under various operational conditions.The analysis reveals that the three-clamp configuration generally provides superior vibrational stability, particularly in the lateral(Y) and vertical (Z) directions, reducing the risk of resonance and dynamic instabilities. In contrast, the two-clamp setup showsincreased vibration levels, especially around 580 Hz, highlighting a potential resonance issue that could lead to structural failureover time. The study finds that while the RPS experiences increased vibrational stress with the two-clamp configuration,potentially impacting measurement accuracy and reliability, the Mechanical Dump Valve (MDV) demonstrates relatively stableperformance between both configurations.The findings suggest that the three-clamp arrangement offers more robust performance, particularly in mitigating vibrations andpreventing resonance, thus enhancing the durability and reliability of the fuel rail system. Recommendations include further PowerSpectral Density (PSD) analysis, shaker tests, and Goodman stress analysis to ensure the two-clamp setup remains viable underpractical conditions. This study contributes valuable insights for optimizing fuel rail support structures in diesel engines, withimplications for reducing manufacturing complexity while maintaining component integrity.